SINERGI AGAMA DAN SAINS: Suatu Paradigma Menuju Era Globalisasi Pendidikan - Muhammad Wayong (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
Modern scientific theory today finds itself quite close to the Qur'an. One reason for this is that science has not been able to produce theories or experiments that fundamentally contradict the Qur'an. Another reason for the harmony between the Qur'an and science is the presence in the Qur'an itself of very clear and positive encouragement to contemplate and investigate the world around us. However, the Qur'an goes beyond simply encouraging all human beings to be aware of the natural world. The non-Muslims in the West have already been advanced in this respect, but…why are Muslims left far behind?